Conservation Education for Elementary School Students - Soenarno, Sri Murni; Miranti, Astari (Edukasi, 2021)
The success of a sustainable development program requires support from nature conservation efforts. It happens because one of the assets for development is natural resources. Pro-conservation people are needed to ensure the sustainability of the nature conservation program is a success. Therefore, conservation education is urgent to be learned in school. The purpose of this study was to observe the responses of elementary school students and teachers in studying nature conservation concepts. The research methods were using the experimental treatment in elementary schools in Jakarta and qualitative analysis. The results showed that both of the students and teachers gave positive responses to learn nature conservation conveyed through various games because the learning situation was amusing and unique. The use of a combination of learning methods is following constructivist learning theory.